Existential Absurdity and Alienation in Kafka’s the Metamorphosis and Hedayat’s the Blind Owl - Davachi, Azadeh (2009)
This study intended to illustrate and compare the specific existential elements such as absurdity and alienation portrayed by Hedayat and Kafka in The Metamorphosis and The Blind Owl. Elucidating how the two authors portrayed these notions in similar or different ways led to the idea that the selected works were similar to each other in terms of existential notions such as absurdity and alienation. The method utilized in this thesis was based on the comparative literature and the two works were treated as the surreal fictions since the characters and incidents were not real. In addition, this study delineated the fact that Hedayat and Kafka employed philosophy of existentialism to testify the perplexed situation of human being’s condition in the contemporary world. Both authors, Kafka and Hedayat, suffered from the modern society’s complexities and tortures that captured their daily lives and also they endured the lack of mutual love and relationship among the members of their families and societies; thereby, they reflected all these concerns in the same way showing how contemporary man tolerates hardships imposed by alienation and world absurdity in a similar way and on the basis of existentialism.